Leak Detection in Liquid Pipeline using Flow Monitoring Method - Wahid, Abdul Hakim (IRC, 2018)
Leak detection is a current field of technology that is used alongside standards and practices to help monitor and maintain continual operation of transporting oil, gases, and other fluid products. Pipeline networks that run across long distances are the safest as well as the most economic mode of transportation. Since many of these products are required to be used by the population nonstop, pipelines that are used as long distance transporting tools must have high demands of reliability, safety, and efficiency. The research focuses on mix of flow monitoring and balancing methods because it is mainly small-scale design and due to cost relative and field instrumentation availability. The starting pipe where the liquid enters will be considered the “master or base” pipe and the flow meter will gather data at that point and communicate wirelessly with the another pipe, considered the “exit” pipe. The exit pipe will be used to read the fluid data and between the base and exit point, compute if there is any imbalance between the two. In between both flow meter pipes is another pipe which is connected to a valve. This pipe acts as a “leak” by opening the valve to allow fluids to escape. Computational algorithms written in C-language on the Arduino development environment will infer a leak when the imbalance occurs and display to the user on LCD screen of the situation. The experimental result shows that the single leakage with different flow condition. In the future, it is recommended to continue leak detection include with the location of the leak and apply cloud monitoring system to monitor, gather, process real-time data and alert the user at the same time.